TRAINING ON THE PRODUCTION OF NATURAL DISHWASHING SOAP FROM PANDAN LEAVES AND LIME IN RIAK SIABUN 1 VILLAGE, SELUMA DISTRICT, BENGKULU - Gusriani, Ika (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2024)
The dishwashing soap commonly found in society generally consists of a mixture of alkali and foaming agents that often cause skin irritation. Due to this issue, a training activity has been organized to teach the production of dishwashing soap using natural ingredients readily available in the surrounding environment, such as pandan leaves and lime. The objective of this activity is to provide training on the utilization of pandan leaves and lime in the production of environmentally friendly dishwashing soap to the members of the Women’s Community Empowerment Group (PKK) of Riak Siabun 1 Village, Sukaraja District, Seluma Regency, Bengkulu Province. This activity is expected to serve as an educational tool and potential business opportunity for the PKK members, maximizing the use of locally available materials, and thus enhancing their economic values. The method employed in this training activity involves socialization and active participation from PKK members of Riak Siabun 1 Village.